2019
DOI: 10.1111/dom.13843
|View full text |Cite
|
Sign up to set email alerts
|

A novel specific peroxisome proliferator‐activated receptor γ (PPARγ) modulator YR4‐42 ameliorates hyperglycaemia and dyslipidaemia and hepatic steatosis in diet‐induced obese mice

Abstract: AimsTo evaluate a novel tetrahydroisoquinoline derivative YR4‐42 as a selective peroxisome proliferator‐activated receptor γ (PPARγ) modulator (SPPARM) and explore its anti‐diabetic effects in vitro and in vivo.Materials and methodsUsing two standard full PPARγ agonists rosiglitazone and pioglitazone as controls, the PPARγ binding affinity and transactivation action of YR4‐42 were evaluated using biochemical and cell‐based reporter gene assays. The capacity of YR4‐42 to recruit coactivators of PPARγ was also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…A new drug class, selective PPAR modulators (SPPARM), is now under development (e.g. INT-131 besylate [CHS-131 [17]], MK-0533 [18], YR4-42 [19]). Preclinical data have shown that SPPARM, compared with thiazolidinedione PPAR-γ full agonists, exert similar effects of glucose and lipid lowering at smaller doses but without causing weight gain and fluid retention, thus reducing side effects and serious safety concerns [18,19].…”
Section: Nuclear Hormone Receptor Agonistsmentioning
confidence: 99%
“…A new drug class, selective PPAR modulators (SPPARM), is now under development (e.g. INT-131 besylate [CHS-131 [17]], MK-0533 [18], YR4-42 [19]). Preclinical data have shown that SPPARM, compared with thiazolidinedione PPAR-γ full agonists, exert similar effects of glucose and lipid lowering at smaller doses but without causing weight gain and fluid retention, thus reducing side effects and serious safety concerns [18,19].…”
Section: Nuclear Hormone Receptor Agonistsmentioning
confidence: 99%
“…Repressive PPARγ modulators acting as inverse agonists are suggested as promising therapeutic options in obesity management and are associated with enhancement in bone formation and improved WAT metabolic functions [ 9 , 48 , 59 , 60 ]. Furthermore, recent insights into the structural mechanisms of the PPARγ repressive function [ 48 ] permit better understanding of the interpretation of the interactions between chemical ligands and PPARγ protein.…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ, the peroxisome proliferator activated receptor (PPAR), is one of the subtypes of PPAR as an important nuclear receptor in cells responsible to regulate glycolipid metabolism key transcription factors of metabolic related genes. 46 PPARγ has adipose tissue specificity and can be activated by fatty acids and exogenous peroxisome proliferators to regulate the expression of enzymes involved in lipid metabolism. PPARγ is induced before the transcriptional activation of many adipocyte genes and plays an important role in fat cell differentiation.…”
Section: Food and Function Papermentioning
confidence: 99%